A Huge Vaginal Prolapse of Uterine Leiomyoma Complicated with Cervical Inversion: A Case Report - Dewi, Ratih Frastika; Farida, Leny Silviana (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Uterine fibroids are non-malignant neoplasms originating from the smooth muscle cells of the uterus, and they represent the most prevalent tumor seen within the female reproductive system. The primary established approach to manage this condition is surgical interventions, specifically myomectomy, hysterectomy, or hysteroscopic removal of small subserous nodules. Occasionally, submucous fibroids may protrude through the cervical os, thereby enabling the feasibility of performing a vaginal hysterectomy. Case Presentation: The clinical presentation of a 44-year-old multiparous woman who arrived with symptoms of vaginal bleeding and a sizable mass protruding through the vaginal opening. The patient underwent an emergency vaginal extraction to remove the mass measuring 24 cm in the emergency room and a scheduled for elective surgery. During the procedure, uterine inversion was found with a muscle bundle around the corpus uteri and a fourth-grade perineal tear. This patient was also planned for a total abdominal hysterectomy and bilateral-salphyngo-oophorectomy procedure, along with Haultain's procedure and perineal repair. The patient exhibited favorable surgical outcomes. Conclusion: Hysterectomy is the preferred therapy for prolapsed pedunculated submucous myoma. It has been seen that even exceptionally big nascent myomas can be effectively removed using vaginal means.